IL-4 functionalized titanium dioxide nanotubes modulate the inflammatory response of macrophages. Issue 17 (21st November 2020) - Yan, Xufeng; Shen, Ke; Tang, Qiang; Fang, Xingtang; Zhang, Chunlei; Zhu, Zhaojing; Hou, Yanhua; Lai, Min
Abstract: Inflammatory response is an essential part of optimal tissue-implant integration and the regeneration process. Due to their highly plastic properties, macrophages display phenotypic changes during inflammatory signaling. Investigating these changes on implant surfaces is essential for evaluating implant stability and longevity. In order to control macrophage polarization, IL-4 was conjugated to titanium dioxide nanotubes (TNTs) through polydopamine, and successful fabrication was checked by scanning electron microscopy (SEM), atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS) and contact angle, respectively. In vitro experiments including immunofluorescence staining, cell proliferation, the expression of genes associated with pro-inflammatory M1 phenotype (tumor necrosis factor-alpha (TNF-α), Interleukin-18 (IL-18)) and cytokines related to the anti-inflammatory M2 phenotype (IL-4 and IL-10), and the production of nitric oxide (NO) and cytokines TNF-α, IL-10 were detected. Macrophage response showed that IL-4 functionalized TNTs favored macrophage polarization towards an anti-inflammatory M2-phenotype. This study provides a new strategy for use in medical devices and the development of advanced nano-biomaterials in immunotherapy applications.